1997
DOI: 10.1038/sj.onc.1201039
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Gas6 as a ligand for Mer, a neural cell adhesion molecule related receptor tyrosine kinase implicated in cellular transformation

Abstract: Mer/Nyk/Eyk is an orphan receptor tyrosine kinase expressed at high levels in monocytes and cells derived from epithelial and reproductive tissues. Overexpression of Mer has been associated with lymphoid malignancies. Here we identify Gas6, the product of a growth arrest speci®c gene, as a ligand for Mer. Gas6 has previously been shown to activate both Axl and Rse/Tyro3, two other receptor tyrosine kinases in the same family as Mer. The apparent relative association and dissociation rate constants of Gas6 for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
139
0

Year Published

1999
1999
2011
2011

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 179 publications
(144 citation statements)
references
References 20 publications
5
139
0
Order By: Relevance
“…Interactive docking with a homology model of the AXL kinase domain and the c-Met kinase domain demonstrated that IM did not bind these RTKs, thus providing an explanation for IM resistance. AXL (Greek word anexelekto or uncontrolled), a transforming gene, was isolated from patients with chronic myelogenous leukemia (CML) (O'Bryan et al, 1991) and is a member of a Ufo/AXL subfamily of RTKs that includes Mer/Nyk/ Eyk and Rse/Tyro3 (Chen et al, 1997). It is a multidomain glycoprotein (896 amino acids) and consists of an extracellular region (425 amino acids) composed of two immunoglobulin-like domains and two fibronectin type III domains, a transmembrane a-helical domain and a c-terminal tyrosine kinase domain (Stitt et al, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…Interactive docking with a homology model of the AXL kinase domain and the c-Met kinase domain demonstrated that IM did not bind these RTKs, thus providing an explanation for IM resistance. AXL (Greek word anexelekto or uncontrolled), a transforming gene, was isolated from patients with chronic myelogenous leukemia (CML) (O'Bryan et al, 1991) and is a member of a Ufo/AXL subfamily of RTKs that includes Mer/Nyk/ Eyk and Rse/Tyro3 (Chen et al, 1997). It is a multidomain glycoprotein (896 amino acids) and consists of an extracellular region (425 amino acids) composed of two immunoglobulin-like domains and two fibronectin type III domains, a transmembrane a-helical domain and a c-terminal tyrosine kinase domain (Stitt et al, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, we found pentraxin 3 (also known as TSG-14), which has been described as a soluble pattern recognition receptor for fungal pathogens [26], to be strongly up-regulated by IL-10. Two further proteins connected with the uptake of autoantigens by the phagocytosis of apoptotic cells are c-mer [27], a receptor tyrosine kinase, and its ligand Gas6 [28,29]. Both are up-regulated by IL-10 in vitro and in vivo.…”
Section: Phagocytosismentioning
confidence: 99%
“…Axl is a RTK de®ning a subfamily of RTK with Rse/Sky, c-Mer/Nyk and Rek (Biscardi et al, 1996;Graham et al, 1994;Ling and Kung, 1995;Mark et al, 1994). More recent studies have shown that Gas6 can similarly bind and activate Rse/Sky and Mer RTK, although with lower a nity (Chen et al, 1997;Mark et al, 1996;Nagata et al, 1996;Ohashi et al, 1995). Gas6 was shown to act as a growth factor for ®broblasts, Schwann cells, chondrocytes, thyroid and vascular smooth muscle cells (Goruppi et al, 1996;Li et al, 1996;Loeser et al, 1997;Nakano et al, 1995;Tanaka et al, 1998).…”
Section: Introductionmentioning
confidence: 99%